Inovasi Pengembangan Pemasaran Produk Susu Kambing Etawa di Dusun Jengglik - Ahmad Akhsinil Umam; Yeny Fitriyani; Achmad Nur Alfianto (Warta Pengabdian Andalas, 2023)
Community empowerment initiatives are pivotal in bolstering the financial stability of rural communities, particularly those facing challenges in marketing local products such as fresh milk. One of the strategic actions taken for the village populace involves enhancing the marketability of Etawa goat milk—a product with significant demand. The principal objective of this service activity is to inject innovation into the sales techniques of Jegglik Village's community outputs. It was achieved through the creation of distinctive logos or labels and leveraging Google Maps to extend the customer base, thereby amplifying the visibility of Etawa goat milk production far and wide. The approach employed in these community service efforts was Asset-Based Community Development (ABCD), which focuses on fostering social cohesion and enabling community-led environmental and economic development, also known as Community-Driven Development (CDD). The outcomes of this initiative have been markedly positive, yielding beneficial impacts for the community, such as expanded market reach and the ability to forge contractual relationships with milk production enterprises.